Property Revisited: Or, Let Us Help History Take Another Direction - Ritsema, Jan; Šišovski, Jordan (Identities: Journal for Politics, Gender and Culture, 2016)
Author(s): Jan Ritsema | Јан Ритсема Title (English): Property Revisited: Or, Let Us Help History Take Another Direction Title (Macedonian): Преиспитана сопственост: Или ајде да ѝ помогнеме на историјата да фати друг правец Translated by (English to Macedonian): Jordan Šišoski | Јордан Шишоски Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 12, No. 1-2 (Winter 2015 - Summer 2016) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 36-59 Page Count: 23 Citation (English): Jan Ritsema, “Property Revisited: Or, Let Us Help History Take Another Direction,” Identities: Journal for Politics, Gender and Culture, Vol. 12, No. 1-2 (Winter 2015 - Summer 2016): 36-57. Citation (Macedonian): Јан Ритсема, „Преиспитана сопственост: Или ајде да ѝ помогнеме на историјата да фати друг правец“, превод од англиски Јордан Шишоски, Идентитети: списание за политика, род и култура, т. 12, бр. 1-2 (зима 2015 - лето 2016): 36-59.